The role of media campaigns in raising women’s awareness of breast cancer “Algerian women as a model - nasri, manel; saidoun, lylia (Journal of Social Sciences and Humanities, 2022)
The media, today considered as an important means of influence and education, especially in the health sector; seek to promote individual and community health through education and awareness. Addressing the entire society, especially to women; the media is helping to raise awareness about many diseases, including breast cancer. The latter has become a real threat to women's health as well as to public health. To combat this scourge, the media must play an important role in prevention, education and awareness. Hence the role of information and awareness campaigns in maintaining a healthy life and the transmission of appropriate knowledge. This contribution focuses on the role of information campaigns in raising awareness of breast cancer screening, and building awareness among Algerian women.